Improving the reliability of synchronous electric motors through monitoring of excitation parameters and winding temperature - Chalyi, O. (Problems of Informatization and Management, 2025)
The article examines the influence of excitation parameters and thermal conditions on the reliability of synchronous electric motors. Analytical dependencies are developed to describe the variation of the electromagnetic torque as a function of the excitation current, as well as thermal models that take into account heat losses in the windings. An integrated mathematical model is proposed for evaluating the failure rate of the motor, considering the combined effect of electrical and thermal factors. A monitoring system approach is presented, providing real-time control of excitation and temperature parameters to enable timely detection of pre-failure operating modes. The obtained results can be applied to improve the durability, energy efficiency, and fault-free operation of synchronous machines in industrial electric drives.